Simultaneous Control of NOx-Soot by Substitutions of Ag and K on Perovskite (LaMnO3) Catalyst - Ganesh Chandra Dhal; Subhashish Dey; Devendra Mohan; Ram Prasad (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
The different Ag and K substituted perovskite catalysts including base catalyst were LaMnO3 by the solid state method and the diesel soot was prepared in the laboratory. Their structures and physico-chemical properties were characterized by X-ray diffraction (XRD), BET, SEM, H2-TPR, and XPS techniques. The Ag Substituted at A-site perovskite structured catalysts are more active than other type of catalysts for the simultaneous soot-NOX reaction, When Ag and K are simultaneously introduced into LaMnO3 catalyst, soot combustion is largely accelerated, with the temperature (Tm) for maximal soot conversion lowered by at least 50 °C, moreover, NOX reduction by soot is also facilitated. The high activity of La0.65Ag0.35MnO3 perovskite catalyst is attributed to presence of metallic silver in the catalyst. The activity order of Ag doped LaMnO3 is as follows La0.65Ag0.35MnO3 > La0.65Ag0.2MnO3 > La0.65Ag0.4MnO3 > La0.65Ag0.1MnO3. The dual substitution of silver and potassium in place of La in LaMnO3 gives better activity than only silver doped catalyst. In a series of La0.65AgxK1-xMnO3, the optimum substitution amount of K is for x=0.25. The single and doubled substituted perovskite catalyst proved to be effective in the simultaneous removal of NOX and soot particulate, the two prevalent pollutants in diesel exhaust gases in the temperature range 350-480 °C.